Intraocular pressure and its normal range adjusted for ocular and systemic parameters: the Beijing Eye Study 2011 - Wang, Ya Xing; Jonas, Jost B. (PLOS ONE, 2018)
PURPOSE: To examine the distribution of intraocular pressure (IOP) in a normal population and the associations of IOP with other ocular and systemic parameters. - METHODS: Out of 3468 participants of the population-based cross-sectional Beijing Eye Study 2011 we selected those individuals without glaucomatous optic neuropathy. The study particpants underwent a detailed ophthalmologic and systemic examination. IOP was measured by air puff non-contact tonometry. - RESULTS: The study included 3135 eyes of 3135 participants with a mean age of 64.1 ± 9.6 years (mean ± standard deviation). The mean IOP was 14.7 ± 2.8 mmHg. The 95% percentile and 97.5% percentile of the IOP distribution decreased from 20 mmHg / 21 mmHg in individuals aged 40 to 54 years to 18 mmHg / 19 mmHg in individuals aged ≥80 years. In multivariable analysis, higher IOP was associated with the systemic parameters of younger age (P<0.001), higher blood concentration of glucose (P = 0.03) and triglycerides (P<0.001), higher diastolic blood pressure (P<0.001), higher pulse rate (P = 0.003) and higher quantity of alcohol consumption (P = 0.004), and with the ocular parameters of larger central corneal thickness (P<0.001), more myopic refractive error (P = 0.01) and steeper anterior corneal curvature radius (P = 0.006). IOP decreased significantly by 0.50 mmHg and 0.76 mmHg for each increase in age by 10 years and each increase in corneal curvature radius by 1.0 mm, respectively. The range of the mean ± 2 standard deviations of the IOP adjusted for the parameters of the multivariable model was 9.0 to 18.1 mmHg versus 9.2-20.2 mmHg for the unadjusted IOP. In the age group of 50 to 55 years, the age-adjusted IOP range (mean ± 2 standard deviations) was 9 to 18 mmHg, and in the age group of ≥75 years, it was 8 to 18 mmHg. - CONCLUSIONS: IOP physiologically depends on a multitude of systemic and ocular factors including age and blood pressure. These physiological associations of the IOP may be taken into account in the definition of the normal range of the IOP.
Gesehen am 19.06.2019